Facilitating the Use of Tools with the National Meteorological Agencies in AICCRA Countries - Rose, Alison; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Throughout 2022, the International Research Institute for Climate and Society (IRI) has enhanced the capacity, skills, and expertise of regional and national meterological agencies in sub-Saharan Africa through a number of activities. In partnership with other AICCRA teams, IRI has co-developed and co-led a number of trainings for the national and regional meteorological agencies in AICCRA countries and beyond, all of which support these agencies in strengthening the reach, impact, quality, and decision-relevance of climate information and services in the agricultural system.